Re‐using bauxite residues: benefits beyond (critical raw) material recovery. Issue 9 (29th June 2018) - Ujaczki, Éva; Feigl, Viktória; Molnár, Mónika; Cusack, Patricia; Curtin, Teresa; Courtney, Ronan; O'Donoghue, Lisa; Davris, Panagiotis; Hugi, Christoph; Evangelou, Michael WH; Balomenos, Efthymios; Lenz, Markus
Abstract: Since the world economy has been confronted with an increasing risk of supply shortages of critical raw materials (CRMs), there has been a major interest in identifying alternative secondary sources of CRMs. Bauxite residues from alumina production are available at a multi‐million tonnes scale worldwide. So far, attempts have been made to find alternative re‐use applications for bauxite residues, for instance in cement / pig iron production. However, bauxite residues also constitute an untapped secondary source of CRMs. Depending on their geological origin and processing protocol, bauxite residues can contain considerable amounts of valuable elements. The obvious primary consideration for CRM recovery from such residues is the economic value of the materials contained. However, there are further benefits from re‐use of bauxite residues in general, and from CRM recovery in particular. These go beyond monetary values (e.g. reduced investment / operational costs resulting from savings in disposal). For instance, benefits for the environment and health can be achieved by abatement of tailing storage as well as by reduction of emissions from conventional primary mining. Whereas certain tools (e.g. life‐cycle analysis) can be used to quantify the latter, other benefits (in particular sustained social and technological development) are harder to quantify. This review evaluates strategies of bauxite residue re‐use / recycling and identifies associated benefits beyond elemental recovery. Furthermore, methodologies to translate risks and benefits into quantifiable data are discussed. Ultimately, such quantitative data are a prerequisite for facilitating decision‐making regarding bauxite residue re‐use / recycling and a stepping stone towards developing a zero‐waste alumina production process. © 2018 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.